The Rise of China-Indonesia Relationship: Soft Power, Resources, and Prospect in the Future - Umagapi, Juniar Laraswanda (Universitas Diponegoro, 2017)
China is the emerging powers that many people believe that in the many years later they will be the most productive country with the fastest growing economic development in the world. As a consequence, China would be the main actor for global integrations as well as one of strategic partners for Indonesia. This research employs qualitative research method to understand which aspect influence the most towards Indonesia and China partnership. This paper will show the future partnership between China and Indonesia in economic and socio-cultural aspect.Keywords: China, Indonesia, emerging powers, economic, integration, socio-cultural